2019
DOI: 10.1021/acsomega.9b02497
|View full text |Cite
|
Sign up to set email alerts
|

Gas–Liquid–Solid Migration Characteristics of Gas Hydrate Sediments in Depressurization Combined with Thermal Stimulation Dissociation

Abstract: The exploitation of natural gas hydrate is always hindered by the migration of water and sands due to gas production. Depressurization combined with thermal stimulation is an effective method for hydrate dissociation. This paper reported the influence of gas–liquid–solid migration on morphological change of hydrate sediments in natural gas production using visualization method. Different backpressures combined with thermal stimulation methods were applied to simulate natural gas hydrate exploitation. Pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…It is however known that gas hydrate growth and dissociation are accompanied by changes in bulk volumes in sediments, loss of sediment strength and subsidence of ground surfaces 37 . Experiments of hydrate growth and dissociation in sediments have shown that the sediment volume will remain expanded compared to initial sediment volume after dissociation leaving a permanent widening of pores, fractures and fissures 38 . The conceptual model of mound growth and crater formation presented in Andreassen, et al 5 focussing on the same craters and mounds as this study, explains that during more widespread and thicker gas hydrate stability conditions during the last glaciation, growth of gas hydrates in pore spaces and fractures, exerted pressure on the sedimentary lattice.…”
Section: Discussionmentioning
confidence: 99%
“…It is however known that gas hydrate growth and dissociation are accompanied by changes in bulk volumes in sediments, loss of sediment strength and subsidence of ground surfaces 37 . Experiments of hydrate growth and dissociation in sediments have shown that the sediment volume will remain expanded compared to initial sediment volume after dissociation leaving a permanent widening of pores, fractures and fissures 38 . The conceptual model of mound growth and crater formation presented in Andreassen, et al 5 focussing on the same craters and mounds as this study, explains that during more widespread and thicker gas hydrate stability conditions during the last glaciation, growth of gas hydrates in pore spaces and fractures, exerted pressure on the sedimentary lattice.…”
Section: Discussionmentioning
confidence: 99%
“…The later experiments regarding sand production behaviors mainly focused on (1) fines migration and its influences on physical properties of the host sediment from both macro-scale , and microscale perspectives; (2) Multilateral coupling effect between depressurization strategies and particle migration. (3) Influences of sand-control devices on fines production, as well as fine-induced plugging of wellbore equipment. (4) Influences of interlayered heterogeneous strata characteristics on sand production behaviors …”
Section: Mechanisms Of Sandingmentioning
confidence: 99%
“…This was a pioneering work, although we would now conclude that the results are limited, or at least not ideal, to cover all sanding mechanisms for HBS since sand production also arose in conventional natural gas production reservoirs with barely water production. 74,75 The later experiments regarding sand production behaviors mainly focused on (1) fines migration and its influences on physical properties of the host sediment from both macroscale 56,76 and microscale 77 perspectives; (2) Multilateral coupling effect between depressurization strategies and particle migration. 77−80 (3) Influences of sand-control devices on fines production, as well as fine-induced plugging of wellbore equipment.…”
Section: Mechanisms Of Sandingmentioning
confidence: 99%
“…In addition to hydrate blockages in pipelines that need to be dissociated, the natural gas hydrates also decompose continuously during the extraction process, which can lead to engineering geological disasters such as subsea stratum deformation, platform tilt and sinking, and climate change. Therefore, many scholars have studied the decomposition characteristics of hydrate particles in high-pressure reactors or porous media by thermal and pressure methods. ,− Among them, in addition to reflecting the decomposition by structural morphology, temperature signalization, and pressure signalization, some scholars also monitored the decomposition process of the hydrate by the change of resistivity (or conductivity), which is a physical quantity that can well reflect the process. Zatsepina et al , monitored the nucleation and decomposition of CO 2 hydrate in porous media by the resistance method.…”
Section: Introductionmentioning
confidence: 99%